2018
DOI: 10.1111/manc.12229
|View full text |Cite
|
Sign up to set email alerts
|

Entry under an Information‐Gathering Monopoly

Abstract: The effects of information-gathering activities on an entry model with asymmetric information are analysed. The baseline game is a classical entry game where an incumbent monopoly faces potential entry by a firm without knowing for certain whether this potential entrant is weak or strong. If the entrant decides to enter, the incumbent must compete with him and decide whether to accommodate or to fight. The paper extends this entry game and considers that the monopoly credibly informs the entrant that she is ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In this sense, this intelligence and security service has defined a broad program to counter economic espionage. 4 The present paper advances the theoretical analysis of the interaction between economic espionage and counter-espionage based on ruining measures.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In this sense, this intelligence and security service has defined a broad program to counter economic espionage. 4 The present paper advances the theoretical analysis of the interaction between economic espionage and counter-espionage based on ruining measures.…”
Section: Introductionmentioning
confidence: 95%
“…This strand of research found market circumstances under which the latter is smaller than the former and, therefore, regulation of entry might be desirable. Two prominent early contributions along these lines are Mankiw and Whinston (1986) and Suzumura and Kiyono (1987) Barrachina (2019). They focused on a context, not necessarily characterized by international free trade, in which an incumbent wishes to deter a potential entrant from entering the market.…”
Section: Related Literaturementioning
confidence: 99%
“…Wang, Gurnani, and Erkoc ((2016)) analyzed the role of pricing and branding in an incumbent firm's decision when facing competition from an entrant firm with limited capacity, finding that in some cases, the incumbent may even increase its price and successfully deter entry by investing in the consumers' reference for its product. Other scholars have made contributions to the knowledge about the competition of the incumbent and the potential entrant (Guo & Ma, 2018; Barrachina, 2019; Huberts et al 2019). However, few of them have studied the competition of the incumbent and the potential entrant while taking business expansion in two‐sided markets into consideration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The above examples motivate us to study the competition between potential entrant platforms and incumbent platforms in the case of business expansion 5 . In recent years, interest in the competition of incumbents and potential entrants has increased sharply (Bakos & Brynjolfsson, 2000,Barrachina, 2019, Huberts, Dawid, Huisman, and Kort ; 2019,2017). More specifically, Bakos and Brynjolfsson (2000) studied different types of competition, including upstream and downstream competition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation